A Mobile Teaching Method of Ideological and Political Education in Colleges and Universities Based on Android Platform. (11th April 2022) - Peng, Yu; Zeng, Yan
Abstract : With the advent of mobile Internet technology, mobile teaching platforms have emerged as the times require and are actively applied in the teaching platform, which greatly enhances the effectiveness of teaching. However, many concerns remain in the integrated development of ideological and political education and mobile teaching platforms, such as improving instructors' information literacy and improving classroom-platform coordination. The integration of teaching and platforms is not high, the main role of students is not paid enough attention, and platform functions need to constantly improve the lack of fusion effect evaluation mechanism, etc. In order to address these issues, it is necessary to investigate the integration and development of the two from the perspectives of improving teachers' information literacy, strengthening online and offline interaction, creating a platform with ideological and political characteristics, implementing the "education-oriented" concept, continuously optimizing platform functions, and developing a scientific evaluation mechanism. Only by following the road will we be able to continue to develop their deep integration and, as a result, increase the teaching quality platform.